2017
DOI: 10.1111/bcp.13250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ezetimibe on plasma adipokines: a systematic review and meta‐analysis

Abstract: The results suggested that ezetimibe add-on to statin therapy is associated with an enhanced TNF-α-lowering effect compared with statin monotherapy. Owing to the emerging role of TNF-α in the pathogenesis of metabolic disorders, further investigations are required to unveil the translational relevance of this TNF-α-lowering effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
(166 reference statements)
0
12
0
Order By: Relevance
“…The global epidemic of obesity is accompanied by a variety of health complications, in large part due to the accumulation of excessive adipose tissue that results in an imbalance in the expression of hormones, pro‐ and anti‐inflammatory adipokines and cytokines . These specific fat‐related hormones mediate vascular changes in obesity, which is an important risk factor for diabetes mellitus, metabolic syndrome and cardiovascular diseases . Weight loss in overweight and/or obese people increases health span and quality of life while also improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global epidemic of obesity is accompanied by a variety of health complications, in large part due to the accumulation of excessive adipose tissue that results in an imbalance in the expression of hormones, pro‐ and anti‐inflammatory adipokines and cytokines . These specific fat‐related hormones mediate vascular changes in obesity, which is an important risk factor for diabetes mellitus, metabolic syndrome and cardiovascular diseases . Weight loss in overweight and/or obese people increases health span and quality of life while also improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These specific fat-related hormones mediate vascular changes in obesity, which is an important risk factor for diabetes mellitus, metabolic syndrome and cardiovascular diseases. 3 Weight loss in overweight and/or obese people increases health span and quality of life while also improving clinical outcomes. Methods of weight loss include diet, physical activity, drug or herbal medicine therapy, and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Additional to these mechanisms, there is evidence showing that Lp(a) serves as an acute-phase reactant and its biosynthesis is augmented by inflammation 1719 . Ezetimibe is known to possess anti-inflammatory activity and may therefore affect Lp(a) production 20,23 . The involvement of the LDL receptor (LDLR) in the catabolism and clearance of plasma Lp(a) has also been discussed 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that combined ezetimibe (10 mg) and simvastatin (20 mg/8 or 12 wk) therapy did not alter adiponectinemia in nondiabetic HC patients, prediabetic HC subjects, and patients with MetS and vascular disease . In the same way, a recent meta‐analysis of 23 controlled trials did not suggest any significant effect on plasma concentrations of adiponectin, and other adipokines, such as leptin, PAI‐1, and IL‐6, was achieved by adding ezetimibe to statin therapy …”
Section: Discussionmentioning
confidence: 90%
“…20,21,29 In the same way, a recent meta-analysis of 23 controlled trials did not suggest any significant effect on plasma concentrations of adiponectin, and other adipokines, such as leptin, PAI-1, and IL-6, was achieved by adding ezetimibe to statin therapy. 30 Yet, treatment with ezetimibe (10 mg) and simvastatin (10 mg/12 wk, or 40 mg/4 wk) increased plasma levels of adiponectin in HC patients. 20,27 These results suggest that the addition of ezetimibe to statin therapy has differential effects on adiponectinemia depending on statin dosage and the duration of treatment.…”
Section: Discussionmentioning
confidence: 93%